Elevated plasma D-dimer levels in patients with anti-N-methyl-D-aspartate receptor encephalitis - Shao, Yingzhe; Du, Juan; Song, Yajun; Li, Yanfei; Jing, Lijun; Gong, Zhe; Duan, Ranran; Yao, Yaobing; Jia, Yanjie; Jiao, Shujie (Frontiers in Neurology, 2022)
Purpose We aimed to explore the difference in coagulation function between healthy individuals and patients with anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis and its relationship with disease severity. Methods We retrospectively compared coagulation function in 161 patients with first-attack anti-NMDAR encephalitis and 178 healthy individuals. The association between D-dimer levels and disease severity was analyzed using binary logistic regression. Receiver operating characteristic (ROC) curves were used to analyze the predictive value of D-dimer levels for the severity of anti-NMDAR encephalitis. Results Compared to control individuals, patients with anti-NMDAR encephalitis had higher D-dimer levels (median 0.14 vs. 0.05 mg/L, p < 0.001), blood white blood cell (WBC) count (median 8.54 vs. 5.95 × 109/L, p < 0.001), and neutrophil count (median 6.14 vs. 3.1 × 109/L, p < 0.001). D-dimers (median 0.22 vs. 0.10 mg/L, p < 0.001), blood WBC count (median 9.70 vs. 7.70 × 109/L, p < 0.001), neutrophil count (median 7.50 vs. 4.80 × 109/L, p < 0.001), and C-reactive protein (median 2.61 vs. 1.50 mg/l, p = 0.017) were higher; however, eosinophils (median 0.02 vs. 0.06 × 109/L, p < 0.001), and blood calcium (median 2.26 vs. 2.31 mmol/L, p = 0.003) were lower in patients with severe forms of anti-NMDAR encephalitis than in those with mild to moderate forms, and were associated with initial modified Rankin Scale scores. Multivariate analysis showed that D-dimer levels were significantly associated with severity [odds ratio =2.631, 95% confidence interval (CI) = 1.018–6.802, p = 0.046]. The ROC curve was used to analyze the predictive value of D-dimer levels for disease severity. The area under the curve was 0.716 (95% CI = 0.64–0.80, p < 0.001), and the best cut-off value was D-dimer = 0.147 mg/L (sensitivity 0.651; specificity, 0.705). Conclusion Serum D-dimer and neutrophil levels were independent predictors of disease severity in patients with first-attack anti-NMDAR encephalitis.